The Effect of Transformational Leadership and Work Motivation on Teacher Performance at Vocational High School Cileungsi - Destiana Utarindasari; Supriatal; Rofiq Noorman Haryadi (Sharia Business Management Department of STEBIS Bina Mandiri, 2022)
This research was conducted on teachers and educational staff at the Vocational High School Cileungsi, with a population of 68 people and then a sample of 40 people was taken using the Slovin formula, then the data collection technique used simple random sampling technique which is part of the probability sampling technique. The method of data collection was carried out through primary data collection in the form of observations and questionnaires. Secondary data through literature study. Instrument testing is done through validity and reliability tests, classical assumption test is done through normality test, heteroscedasticity test, autocorrelation and multicollinearity test. The data analysis technique uses quantitative data frequency distribution, multiple linear regression analysis, correlation coefficient, coefficient of determination, T test and F test. The results of the study based on the results of the F test processing, it can be concluded that the F value is 14.805 > 5.23 then Ho is rejected and Ha is accepted. With these results, the variables of transformational leadership (X1) and motivation (X2) both have an effect on performance (Y).